ADAPTIVE ART OF THE MODERN POSTER: SOCIAL COMMUNICATION AND ADVERTISING - Колосніченко, О. В.; Остапенко, Н. В.; Єжова, О. В.; Кротова, Т. Ф.; Колосніченко, М. В.; Чжоу , Ч. (Art and Design, 2023)
Purpose: research of the historical development of the poster genre and the concept of social advertising, as well as its position and influence in the modern world. Research of the dominant phenomena of the development of the poster genre as a cultural code of society in certain historical periods. Methodology. Historical-typological, retrospective, analytical methods, as well as image-stylistic and comparative analysis were used for the research. The theoretical and methodological basis determines the systematic approach in the study of the poster genre of world and domestic graphic artists. System-structural and associative methods were also used in the study of artistic and compositional features and semantic resources in the historical development of the poster as a special artistic genre. Results. The analysis is performed and the dominant style as one of the possibilities of influencing the main imaginary components of social life by means of graphic design is investigated. Examples of the specifics of the poster genre and visual aids in the context of social advertising are given, which later becomes an integral part of poster design as an element of project graphics, as well as its combination with the relevant textual presentation of material in the social poster genre. The tasks of the communicative component in creating a poster, its graphic saturation, their combinations to increase the possibilities of differentiated influence in active use in society are considered. It was found that the poster as a specific genre of art in its manifestation is able to express the principled humanistic position and important values of mankind. It has been proven that the modern social poster reproduces an integrated set of effective values related to globalized progress, educational innovations, cultural enrichment, etc., as evidenced by the intensive development of poster art in line with global trends. The scientific novelty of the work lies in a comprehensive approah to the study of environmental social advertising and the peculiarities of the use of compositional principles in poster design. The structural-semantic analysis of visual means and stylistic tendencies in the poster is carried out. The artistic imagery and the main stages of development of the ecological poster, in particular in Ukraine, are considered. It is noted that the intensification of attention to environmental issues and reasonable consumption of resources will significantly contribute to the development of eco- culture of society, especially the younger generation. The practical significance of the study is due to the expansion and deepening of theoretical knowledge of the process of creating a modern poster in accordance with the definition of social advertising and communication, their development and influence on the formation of moral and ethical principles of society. The obtained results allowed to apply elements of a systematic approach to the creation of the most effective social advertising. The presented results are recommended for use in practical project work of graphic designers, as well as in the educational process in the training of artists and designers-scientists in case studies.